Optimisation of a 5-[3-phenyl-(2-cyclic-ether)-methyl-ether]-4-aminopyrrolopyrimidine series of IGF-1R inhibitors. Issue 8 (15th April 2016) - Fairhurst, Robin A.; Marsilje, Thomas H.; Stutz, Stefan; Boos, Andreas; Niklaus, Michel; Chen, Bei; Jiang, Songchun; Lu, Wenshuo; Furet, Pascal; McCarthy, Clive; Stauffer, Frédéric; Guagnano, Vito; et al.
Graphical abstract: Abstract: Taking the pyrrolopyrimidine derived IGF-1R inhibitor NVP-AEW541 as the starting point, the benzyl ether back-pocket binding moiety was replaced with a series of 2-cyclic ether methyl ethers leading to the identification of novel achiral [2.2.1]-bicyclic ether methyl ether containing analogues with improved IGF-1R activities and kinase selectivities. Further exploration of the series, including a fluorine scan of the 5-phenyl substituent, and optimisation of the sugar-pocket binding moiety identified compound33 containing ( S )-2-tetrahydrofuran methyl ether 6-fluorophenyl ether back-pocket, and cis - N -Ac-Pip sugar-pocket binding groups. Compound33 showed improved selectivity and pharmacokinetics compared to NVP-AEW541, and produced comparable in vivo efficacy to linsitinib in inhibiting the growth of an IGF-1R dependent tumour xenograft model in the mouse.